2022
DOI: 10.1186/s12874-022-01730-6
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of the safety from allergic rhinitis trials registered on ClinicalTrials.gov and in publications: An observational study

Abstract: Background Incomplete and inconsistent reporting of adverse events (AEs) through multiple sources can distort impressions of the overall safety of the medical interventions examined as well as the benefit-risk relationship. We aimed to assess completed allergic rhinitis (AR) trials registered in ClinicalTrials.gov for completeness and consistency of AEs reporting comparing ClinicalTrials.gov and corresponding publications. Methods We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This approach improves the findability of trial outcomes. However, it fails to realise two other key advantages of registry reporting in tabular summary results format compared to journal publication: accelerated reporting timelines, and improved completeness and accuracy of outcome data (20)(21)(22)(23)(24)(25). Thus, while between 2/49 (4%) of trials (Scenario 1) and 2/71 (3%) of trials (Scenario 2) technically met WHO best practices in clinical trial reporting, no trial fully delivered on the benefits of registry reporting.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…This approach improves the findability of trial outcomes. However, it fails to realise two other key advantages of registry reporting in tabular summary results format compared to journal publication: accelerated reporting timelines, and improved completeness and accuracy of outcome data (20)(21)(22)(23)(24)(25). Thus, while between 2/49 (4%) of trials (Scenario 1) and 2/71 (3%) of trials (Scenario 2) technically met WHO best practices in clinical trial reporting, no trial fully delivered on the benefits of registry reporting.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The finding of discrepancies between important aspects of clinical trials involving NSPP, including primary outcomes, in the trial registry and related journal articles points to low transparency and questionable validity of the trials, creating problems in adequate introduction of tested interventions in clinical practice. While the registration mandate by journals, followed by legislative mandates, has greatly increased the transparency of trial protocol information [ 33 , 34 ], the problem of trial registration quality persists, not only in dental medicine, as demonstrated in our study, but in other clinical disciplines [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%